2011
DOI: 10.1016/j.neuroimage.2011.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral mechanisms of human fear generalization

Abstract: While much research has elucidated the neurobiology of fear learning, the neural systems supporting the generalization of learned fear are unknown. Using functional magnetic resonance imaging (fMRI), we show that regions involved in the acquisition of fear support the generalization of fear to stimuli that are similar to a learned threat, but vary in fear intensity value. Behaviorally, subjects retrospectively misidentified a learned threat as a more intense stimulus and expressed greater skin conductance resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
147
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 64 publications
16
147
0
Order By: Relevance
“…Lissek, Bradford, et al (2014) investigated the brain mechanisms of fear generalization using a version of the "rings of varying size" paradigm. Results replicated previous fMRI investigations of fear generalization in humans (Dunsmoor, Prince, et al, 2011;Greenberg et al 2013a,b), revealing a ("positive") gradient in bilateral insula to stimuli resembling the CS+, and a ("negative") gradient in vmPFC to stimuli more closely approximating the CS-. Positive gradients were also found in the dorsomedial prefrontal cortex and bilateral inferior parietal lobule, while negative gradients were found in bilateral hippocampus and precuneus.…”
Section: Perceptual Fear Generalizationsupporting
confidence: 88%
See 2 more Smart Citations
“…Lissek, Bradford, et al (2014) investigated the brain mechanisms of fear generalization using a version of the "rings of varying size" paradigm. Results replicated previous fMRI investigations of fear generalization in humans (Dunsmoor, Prince, et al, 2011;Greenberg et al 2013a,b), revealing a ("positive") gradient in bilateral insula to stimuli resembling the CS+, and a ("negative") gradient in vmPFC to stimuli more closely approximating the CS-. Positive gradients were also found in the dorsomedial prefrontal cortex and bilateral inferior parietal lobule, while negative gradients were found in bilateral hippocampus and precuneus.…”
Section: Perceptual Fear Generalizationsupporting
confidence: 88%
“…In a follow-up fMRI investigation, intensity biases were revealed in brain regions implicated in the acquisition of conditioned fear (CS+ versus CS-) including the insula, thalamus, and striatum (Dunsmoor, Prince, et al, 2011). That is, activity in these regions was enhanced to generalized stimuli of high intensity after, but not before, fear conditioning to a CS+ of intermediate intensity.…”
Section: Nonperceptual-based Fear Generalizationmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent research, the 'generalization' of fear of pain has been suggested as a mechanism by which fear might contribute to the spreading of pain 15, 45, 46 .…”
Section: Psychology Of Multisite Pain 16mentioning
confidence: 99%
“…Generalization of fear of pain occurs when the expectation of a painful sensation is associated with a stimulus that resembles, but is not identical to, the original stimulus 15 . Generalization of fear of pain is believed to be associated with increased and sustained vigilance for pain, as a result of deficient safety learning 14, 40 .…”
Section: Psychology Of Multisite Pain 16mentioning
confidence: 99%